FAKTOR_FAKTOR YANG MEMPENGARUHI PERMINTAAN KREDIT USAHA MIKRO KECIL MENENGAH (UMKM) DI PROVINSI ACEH - Yasrizal Yasrizal (Universitas Teuku Umar, 2018)
Industrial growth of micro, small and medium enterprises (MSMEs) is able to absorb higher labors than large industry as the small industry is more labor-intensive instead of the capital intensive. Due to the changes in interest rates, inflation level, and economic growth aggregately influenced the MSME investment sector, the stability of the economic conditions also affected the MSME loan. The data used in this study was secondary data obtained from Bank Indonesia of Aceh during 2010-2015 on a quarterly basis. The dependent variable used was credit value of MSMEs, while the independent variables were interest rate, inflation and economic growth. The data was analyzed by using multiple linear regression models. The result showed that the variable of interest rates and inflation toward credit demand in Aceh has influenced significantly, however the variable of economic growth has not. The correlation coefficient of the inflation variable was amounted to -0.1494 which means that if the inflation increased 1%, the credit demand would be decreased about 0.1494 billion IDR. Besides, the correlation coefficient of interest rate was 0.7395. It means that if the interest rate increased 1%, the amount of credit demand of MSME would be increased about 0.7395 billion IDR. Based on the results of this study, the most influenced variable on credit demand was interest rate.Kata Kunci : Inflasi, Suku Bunga, Pertumbuhan Ekonomi, UMKM